2013
DOI: 10.1167/iovs.12-10950
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Protein Acidic and Rich in Cysteine (SPARC)-Null Mice Exhibit More Uniform Outflow

Abstract: Aqueous outflow in mice is segmental. SPARC-null mice demonstrated a more uniform outflow pattern and decreased collagen fibril diameter. Areas of high flow had less compact juxtacanalicular connective tissue ECM, and IOP was inversely correlated with PEFL. Our data show a correlation between morphology, aqueous outflow, and IOP, indicating a modulatory role of SPARC in IOP regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 44 publications
(56 reference statements)
4
101
0
Order By: Relevance
“…Prior studies have shown that tracer labeling patterns in the trabecular meshwork coincide with the distribution of extracellular matrix (ECM) proteins, such as versican 21 and SPARC, 23 suggesting that accumulation of ECM proteins may influence local hydraulic conductivity through the trabecular meshwork. Morphological correlates of segmental outflow have also been described in bovine, 15 monkey, 16 and human 9,17 eyes where regions of greater tracer labeling coincide with local separation between the endothelial lining of Schlemm's canal and the underlying JCT, which has been described as disrupting the ''funneling'' effect 27 and leads to a local increase in hydraulic conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that tracer labeling patterns in the trabecular meshwork coincide with the distribution of extracellular matrix (ECM) proteins, such as versican 21 and SPARC, 23 suggesting that accumulation of ECM proteins may influence local hydraulic conductivity through the trabecular meshwork. Morphological correlates of segmental outflow have also been described in bovine, 15 monkey, 16 and human 9,17 eyes where regions of greater tracer labeling coincide with local separation between the endothelial lining of Schlemm's canal and the underlying JCT, which has been described as disrupting the ''funneling'' effect 27 and leads to a local increase in hydraulic conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81] As with other aspects of aqueous outflow, segmental flow has dramatic implications on the resistance adjustments that occur during IOP homeostasis. Questions about the site of resistance adjustments, that is, does it occur in high or in low flow regions?…”
Section: Segmental Outflow and Iop Homeostasismentioning
confidence: 99%
“…82,83 SPARC-null mice have a decrease in the collagen fibril diameter within the JCT of the TM, consistent with that observed in the dermis of SPARC-null mice. 33,83 These data suggest a mechanism by which IOP is reduced in SPARC-null mice. Given SPARC's effect on collagen fibril diameter, variation in the spatial expression of SPARC throughout the TM may be a mechanism for the generation of segmental flow that occurs in the human and murine eye.…”
Section: Trabecular Meshworkmentioning
confidence: 78%